The Effect of Environmental Leadership and Environmental Personality on Staffs’ Perception Toward Greening Institutions - Andi Muhammad Subhan (IJEEM - Indonesian Journal of Environmental Education and Management, 2016)
This research is about studying the effect of environmental leadership and environmental personality on staffs’ perception toward greening institutions. There were around 6 research problems have been solved, including dependency between environmental leadership and environmental personality with staffs’ perception toward greening institutions. Therefore, an ex-post facto method by using 2 x 2 factorial designs had been applied. Each cell consisted of 16 staffs from provincial government institutions, South Sulawesi which selected randomly. There were three instruments have been developed such as Environmental Leadership (EL), Environmental Personality (EP), and Greening Institutions (GI) which measured in a scaling form. Its reliable was respectively .991 (EL), .907(EP), and .929 (GI). Data have been analyzed by implementing two-way ANOVA and Chi-Square. Research results show that there is highly significant difference of staffss’ perception toward greening institutions between stafss who perceived their superordinate to have transformational environmental leadership rather than transactional. There is highly difference of staffs’ perception toward greening institutions between staffs who has good and bad environmental personality. There is no significant interaction effect found between environmental leadership and environmental personality on greening institutions. Finally, there is dependency between environmental leadership and environmental personality with greening institutions. Based on these findings, it could be interpreted that staffs’ perception toward greening institutions might have been affected by environmental leadership independently without considering environmental personality. Therefore, if the greening institutions would be improved, environmental personality and environmental leadership could be taken in to consideration separately.